2015
DOI: 10.1097/wco.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the immunopathogenesis of multiple sclerosis

Abstract: A better understanding of immune-mediated mechanisms in the pathogenesis of multiple sclerosis and the contribution of environmental risk factors toward the development of multiple sclerosis will help further improve therapeutic approaches to prevent disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 240 publications
2
105
0
8
Order By: Relevance
“…MS is an autoimmune disease that affects the brain and the spinal cord, and it is characterized by neuroinflammation as well as neurodegeneration caused by the depletion of myelin in the central nervous system (CNS) [80, 81]. The pathogenesis of MS involves Th1 and Th17 responses to myelin antigens [80, 81].…”
Section: Involvement Of Il-27 In the Pathogenesis Of Autoimmune DImentioning
confidence: 99%
See 1 more Smart Citation
“…MS is an autoimmune disease that affects the brain and the spinal cord, and it is characterized by neuroinflammation as well as neurodegeneration caused by the depletion of myelin in the central nervous system (CNS) [80, 81]. The pathogenesis of MS involves Th1 and Th17 responses to myelin antigens [80, 81].…”
Section: Involvement Of Il-27 In the Pathogenesis Of Autoimmune DImentioning
confidence: 99%
“…The pathogenesis of MS involves Th1 and Th17 responses to myelin antigens [80, 81]. The level of IL-27 in the plasma/serum from MS patients was found to be significantly lower than that of healthy controls [82-84], and IL-27 level showed an inverse correlation with the level of plasma IL-17 as well as the frequency of Th17 cells in the blood [82].…”
Section: Involvement Of Il-27 In the Pathogenesis Of Autoimmune DImentioning
confidence: 99%
“…They are known to be mediated by peripherally generated autoreactive T-cells infiltrating into the CNS, where they are re-stimulated by antigen-presenting cells, resulting in local expansion of pathogenic Th1 and Th17 cells, tissue damage to oligodendrocytes, and subsequently, a secondary infiltration of bystander immune cells, controlling the disease's perpetuation (2,3). Regulatory T-cells (Treg) are involved in limiting the activation, proliferation and infiltration of pathogenic effector cells into the CNS (1, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) that is characterized by peripheral inflammatory processes, blood-brain barrier (BBB) breakdown, and immune cell infiltration into the CNS, leading to both axonal damage and demyelination, and ultimately resulting in disability in MS patients [152–154]. Previous studies showed that high salt not only potentiates LPS-induced macrophage activation, including enhanced IL-1α, TNF-α and IL-1β production, but also enhances the development of MS partly through changing the gut microbiome [153, 155160].…”
Section: The Role Of Intestinal Macrophage In Autoimmune Diseasesmentioning
confidence: 99%